Análise longitudinal de sinais e sintomas de piora de asma, função pulmonar e qualidade do ar domiciliar e sua associação com o controle da doença - Costa, Luan dos Santos Mendes (2025)
Introduction: Asthma is one of the leading chronic non-communicable respiratory diseases, affecting individuals of all age groups. Exacerbations are common throughout the course of asthma and contribute to poor disease control. Therefore, asthma control is a crucial outcome measure for effective disease management. Objective: To analyze the association between worsening asthma signs and symptoms, pulmonary function, air quality, and disease control in individuals with asthma. Methods: This observational, longitudinal study is part of a larger research project aimed at identifying predictors of asthma exacerbation. The study included individuals with asthma who had experienced at least one exacerbation in the past year, had no conditions that could compromise data collection, were between 22 and 60 years old, were literate, and resided in the metropolitan region of Fortaleza. Data collection included sociodemographic, anthropometric, and clinical information, as well as the administration of the Asthma Control Questionnaire (ACQ) to assess asthma control and the Mini Asthma Quality of Life Questionnaire (mini-AQLQ) to evaluate quality of life. Pulmonary function was assessed using spirometry. Participants were then remotely monitored for 28 days, with daily assessments of worsening asthma signs and symptoms, heart rate (HR), oxygen saturation (SpO2), and pulmonary function using a peak expiratory flow (PEF) device. Air quality data within participants' homes were also recorded. At the end of each week of remote assessment, the ACQ was administered, and the weekly mean values for each variable were calculated. Results: A total of 34 participants were included (70.6% female, mean age of 37 ± 13 years, and body mass index – BMI of 28.37 ± 5.12 kg/m2). Regarding asthma control, 70.6% of the participants had uncontrolled asthma, as indicated by the Asthma Control Questionnaire (ACQ). Baseline ACQ showed statistically significant, positive, and weak to moderate correlations with weight and height (rs=0.342 and rs=0.344, respectively; p<0.05 for both), and a negative correlation with post-bronchodilator FEV1 (in liters) and peak expiratory flow (PEF) (rs=-0.38; p<0.05 for both). Weekly ACQ showed significant weak to moderate correlations with a higher number of signs and symptoms of asthma worsening upon awakening, as well as with heart rate (HR) and oxygen saturation (SpO2) variables (p<0.05 for all). Additionally, moderate correlation was observed with temperature throughout the week (rs=0.514; p<0.001). Individuals with uncontrolled asthma exhibited higher HR before sleep, higher home temperature, and lower levels of particulate matter of 10.0 μg/m3 (PM10.0) (p<0.05). Conclusion: Asthma control is associated with anthropometric variables, such as weight and height, and pulmonary function measurements. Additionally, HR, SpO2, and home temperature were correlated with weekly ACQ scores. Further studies are needed to confirm these findings.